Identification of Bacteria as Health Indicators of Mangrove Crab (Scylla Serrata) at Farm Suppliers in South Kalimantan - Rimalia, Anny; Kisworo, Yulius; Bahrun, Bahrun; Husinsyah, Husinsyah; hidayat, Ahmad (International Journal of Environment, Agriculture and Biotechnology, 2022)
This study aims to identify the types of pathogenic bacteria in mangrove crabs (Scylla serrata) and determine the health condition of mud crabs (Scylla serrata) at farm supply in South Kalimantan Province. The research method used is a case study, with sampling of mangrove crabs by purposive sampling at the farm supplier by considering the form supplier is already a legal entity, is still active in shipping and the frequency of shipments is quite a lot as well as continuous delivery to domestic and export destinations. For locations, sampling of mangrove crabs (Scylla serrata) was carried out at 3 (three) farm suppliers, namely CV. ACS in Banjarbaru City, CV. Three A's in Banjar Regency and UD. SLM in Banjarbaru City. For bacterial examination, it was repeated three times with the number of crab samples adjusted to the delivery population at the time of the study. The results showed that 15 mud crabs were infected with the pathogenic bacteria Plesiomonas sp (42%) followed by Actinobacillus sp. (39%), Vibrio sp. (16%) and Moraxella sp. (3%). The most common type of pathogenic bacteria infecting the farm supplier CV. ACS is a type of Actinobacillus sp. as many as 5 tails, while on the farm supplier CV. Three A are Plesiomonas sp. and Actinobacillus sp each as many as 5 tails and on farm supplier UD. SLM is a type of Plesiomonas sp as many as 6 tails. The condition of the mud crab (Scylla serrata) is declared physically healthy with the characteristics when the swimming legs are pulled away from the carapace and then released, the legs move quickly to their original position, the eye stalks are very responsive, that is, they enter the orbital area when touched, the mouth does not release foam, color The carapace is bright and does not have a bad smell and there are no pathogenic bacteria found in mud crabs that are harmful to the human body or safe for consumption.